Approximation Properties of Newman Type Interpolation Rational Functions with Fewer Nodes (Analysis in Theory and Applications, 2023)
In the present note, we consider the problem: how many interpolation nodescan be deleted from the Newman-type rational function such that the convergence ratestill achieves.